2013
DOI: 10.1115/1.4024499
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Determination of Single-Phase Forced Convection Coefficients in Microchannels

Abstract: This paper deals with the analysis of the main features of forced microconvection of liquid and gas flows through microchannels. A critical oveiyiew of the main effects that tends to play an important role in the determination of Nusselt number in microchannels is presented. Some experimental data obtained at the Microfluidics Lab of the University of Bologna together with the main results which appeared recently in the open literature both for liquids and gases are used in order to highlight the peculiar char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Convective pressure-driven single phase fluid flows in micro-channels can be studied theoretically by determining the fluid velocity and temperature distribution using the mass, momentum and energy balance equations. If the continuum hypothesis is still valid for the working fluid within the microdevice, the classical formulation of the balance equations can be generally used [4,5].…”
Section: Forced Convection In Microchannelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Convective pressure-driven single phase fluid flows in micro-channels can be studied theoretically by determining the fluid velocity and temperature distribution using the mass, momentum and energy balance equations. If the continuum hypothesis is still valid for the working fluid within the microdevice, the classical formulation of the balance equations can be generally used [4,5].…”
Section: Forced Convection In Microchannelsmentioning
confidence: 99%
“…In this paper, it will be demonstrated that the analysis of forced convection in micro-channels usually needs a combined experimental/numerical approach, as evidenced by Morini and Yang [5] and, more recently, by Wang et al [6]. This is partially due to the problems linked to the problems which afflict the measurement of the local fluid properties within the micro-systems.…”
Section: Introductionmentioning
confidence: 97%
“…Experimental investigations on heat transfer characteristics of gas flow in microchannels have been performed by a number of researchers using most common thermal boundary conditions, namely constant heat flux (CHF) and constant wall temperature (CWT) with emphasis on CHF [9][10][11][12]. The literature was well surveyed and critically reviewed by Lin et al, [10] and Morini et al, [11].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations on heat transfer characteristics of gas flow in microchannels have been performed by a number of researchers using most common thermal boundary conditions, namely constant heat flux (CHF) and constant wall temperature (CWT) with emphasis on CHF [9][10][11][12]. The literature was well surveyed and critically reviewed by Lin et al, [10] and Morini et al, [11]. It is reported that the thermal behavior at microscale of gas and liquid flows through microchannel in terms of convective heat transfer coefficients can be strongly affected by scaling and micro-effects but also by practical issues linked to the geometry of the testing, the real thermal boundary conditions, the presence of fittings and position and type of the sensors, and so on [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation